Down-regulation of Fra a 1.02 in strawberry fruits causes transcriptomic and metabolic changes compatible with an altered defense response. (10th March 2021) - Orozco-Navarrete, Begoña; Song, Jina; Casañal, Ana; Sozzani, Rosangela; Flors, Victor; Sánchez-Sevilla, José F; Trinkl, Johanna; Hoffmann, Thomas; Merchante, Catharina; Schwab, Wilfried; Valpuesta, Victoriano
Abstract: The strawberry Fra a 1 proteins belong to the class 10 Pathogenesis-Related (PR-10) superfamily. In strawberry, a large number of members have been identified, but only a limited number is expressed in the fruits. In this organ, Fra a 1.01 and Fra a 1.02 are the most abundant Fra proteins in the green and red fruits, respectively, however, their function remains unknown. To know the function of Fra a 1.02 we have generated transgenic lines that silence this gene, and performed metabolomics, RNA-Seq, and hormonal assays. Previous studies associated Fra a 1.02 to strawberry fruit color, but the analysis of anthocyanins in the ripe fruits showed no diminution in their content in the silenced lines. Gene ontology (GO) analysis of the genes differentially expressed indicated that oxidation/reduction was the most represented biological process. Redox state was not apparently altered since no changes were found in ascorbic acid and glutathione (GSH) reduced/oxidized ratio, but GSH content was reduced in the silenced fruits. In addition, a number of glutathione-S-transferases (GST) were down-regulated as result of Fra a 1.02-silencing. Another highly represented GO category was transport which included a number of ABC and MATE transporters. Among the regulatory genes differentially expressed WRKY33.1 and WRKY33.2 were down-regulated, which had previously been assigned a role in strawberry plant defense. A reduced expression of the VQ23 gene and a diminished content of the hormones JA, SA, and IAA were also found. These data might indicate that Fra a 1.02 participates in the defense against pathogens in the ripe strawberry fruits.